Cylinder arrangement for raising a carriage and uprights of a mast - LESKOVEC, EDWARD V (1980)
A lift truck having a mast assembly for lifting a load. The assembly includes a first fixed pair of spaced-apart uprights and a second movable pair of spaced-apart uprights with the second pair nested for vertical translation within the first pair, and a carriage coupled to the second pair for vertical translation in relation to the second pair. Two chains, which extend over two sheaves connected to a cross-member fixed to the upper ends of the second pair of uprights, have one end connected to a first hydraulic cylinder and their other end to the carriage. Second and third hydraulic cylinders, behind the first and second pair, are coupled to respective third and fourth sheaves about which extend additional chains having one end connected to the fixed uprights and the other end connected to the movable uprights. The first hydraulic cylinder lifts the carriage in relation to all the uprights and the second and third hydraulic cylinders simultaneously raise the second pair of uprights and the carriage. The second and third hydraulic cylinders are anchored on a cross-brace intermediate the ends of the uprights and acted on by a fourth hydraulic cylinder to tilt the assembly.